Baiying qingmai formulation ameliorates thromboangiitis obliterans by inhibiting HMGB1/RAGE/NF-κB signaling pathways - Zou, Chongchong; Liu, Li; Huang, Chuanqi; Hu, Song (Frontiers in Pharmacology, 2022)
Baiying Qingmai Formulation (BF) is a classical clinical prescription used for decades to treat thromboangiitis obliterans (TAO). Although it effectively relieves pain and ischemic ulcers in patients with TAO, its anti-TAO mechanisms remain unclear. The chemical components of BF were analyzed using high-performance liquid chromatography and the potential targets of the compounds identified in BF were analyzed using molecular docking. Further, the signaling pathways and molecular mechanism of BF in treating TAO were studied using a rat model of TAO. Seven compounds (gallic acid, catechin, chlorogenic acid, caffeic acid, paeoniflorin, quercetin, and paeonol) were identified in BF, and molecular docking predicted their high affinities with HMGB1/RAGE/NF-κB proteins. In in vivo studies, BF not only inhibited the protein expression of HMGB1, RAGE, NF-κB, ICAM-1, and VCAM-1; mRNA levels of HMGB1 and RAGE; and the phosphorylation of ERK and Janus kinase (JNK) in the femoral artery, but also reduced the levels of inflammatory cytokines (IL-6, TNF-α, IL-1β, HMGB1) and stable metabolite (TXB2) of cytokine promoting thrombosis (TXA2) in the plasma. Moreover, BF stimulated the secretion of stable metabolite (6-keto-PGF1α) of cytokine inhibiting thrombosis (PGI2) in the plasma and AKT phosphorylation in the femoral artery. BF inhibited the inflammatory response and thrombosis in the femoral artery, thus reducing the degree of vascular occlusion, which alleviated the symptoms in rats with TAO. Our findings suggest that BF ameliorates TAO by inhibiting the activation of the ERK, JNK, and HMGB1/RAGE/NF-κB signaling pathways and facilitating activation of the AKT signaling pathway, thereby providing novel ideas for the treatment of TAO and essential information for the further development and utilization of BF as a promising drug to treat TAO.